The Influence of Quality, Price, and Atmosphere on Customer Loyalty through Satisfaction at Lime Restaurant - Josephine Melrose Rarome; Hananiel Mennoverdi Gunawan (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
The hotel restaurant industry continues to evolve by offering more than just high-quality food, but also culinary experiences that involve quality service, ambiance, and social interaction. Lime Restaurant at Four Points Tunjungan Plaza Surabaya is one of the hotel restaurants that faces challenges in maintaining repeat customer visits. This study aims to examine the effect of food quality, service quality, ambiance, price & value, and restaurant reputation on customer satisfaction and revisit intention at Lime Restaurant. This study uses a quantitative approach with a survey design, where data is collected through questionnaires distributed to customers who have visited the restaurant. The variables analyzed include food quality, service quality, price & value, ambiance, and restaurant reputation as factors that influence customer satisfaction, revisit intention, and customer loyalty. The analysis techniques used include regression analysis to test the relationship between variables, and Importance-Performance Map Analysis (IPMA) to evaluate improvement priorities. The results of this study are expected to provide strategic insights to improve customer experience and strengthen their loyalty to hotel restaurants.